2022
DOI: 10.4143/crt.2021.332
|View full text |Cite
|
Sign up to set email alerts
|

Chronological Analysis of Acute Hematological Outcomes after Proton and Photon Beam Craniospinal Irradiation in Pediatric Brain Tumors

Abstract: This study aimed to compare the early hematological dynamics and acute toxicities between proton beam craniospinal irradiation (PrCSI) and photon beam craniospinal irradiation (PhCSI) for pediatric brain tumors. Materials and MethodsWe retrospectively reviewed patients with pediatric brain tumors who received craniospinal irradiation (CSI). The average change in hemoglobin levels (ΔHbavg), absolute lymphocyte counts (ΔALCavg), and platelet counts (ΔPLTavg) from baseline values was evaluated and compared betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…PBT as an RT modality was not significantly associated with height restriction. PBT has been preferred for pediatric patients with cancer because it has shown potential benefits, such as lower secondary malignancy [ 20 ] and better hematologic outcomes after RT [ 21 ]. PBT can spare the anterior part of the body when locally irradiated using posterior beams.…”
Section: Discussionmentioning
confidence: 99%
“…PBT as an RT modality was not significantly associated with height restriction. PBT has been preferred for pediatric patients with cancer because it has shown potential benefits, such as lower secondary malignancy [ 20 ] and better hematologic outcomes after RT [ 21 ]. PBT can spare the anterior part of the body when locally irradiated using posterior beams.…”
Section: Discussionmentioning
confidence: 99%
“…PBT as an RT modality was not signi cantly associated with height restriction. PBT has been preferred for pediatric patients with cancer because it has shown potential bene ts, such as lower secondary malignancy [19] and better hematologic outcomes after RT [20]. PBT can spare the anterior part of the body when locally irradiated using posterior beams.…”
Section: Discussionmentioning
confidence: 99%
“…Past studies have shown that hematologic toxicity was less prominent for PBT compared with photon RT during and for 4 weeks after CSI. 17 Yoo et al 25 reported that PBT resulted in a better recovery of the absolute lymphocyte and PLT counts than photon RT. We decided between using the WVB technique or the VBS technique based on the patient's age.…”
Section: Discussionmentioning
confidence: 99%